Indigenous language knowledge management : Indexing phonemes acoustically / Tengku Intan Suzila Tengku Sharif, K. S Teo and Mohd Yusri M. N. - Tengku Sharif, Tengku Intan Suzila; K. S, Teo; M. N., Mohd Yusri (Universiti Teknologi MARA Cawangan Pahang, 2016)
One of the branches of community knowledge management system (CKMS) is regional knowledge, which includes indigenous knowledge. Capturing indigenous knowledge requires internalization of the knowledge where learning by doing is essential. The present study discusses indigenous language knowledge management of the endangered Peninsular Malaysia Orang Asli languages while enabling technologies to document language in use and adopting acoustic analysis for phonological presentation in order to create integrated indigenous language knowledge for grammar establishment leading towards preservation and future revitalization purposes. The aim of the study is to appreciate instrumental analysis as a tool that enables enhancement for future phonological study. The study suggests that to better manage language knowledge is to advance and incorporate instrumental analysis over subjective impressionistic analysis.